Guidelines for increasing the efficiency of research management of Sisaket Rajabhat University - จักรบุตร อริศาพัชร (Research and Development Journal Sisaket Rajabhat University, 2022)
The objectives of this research are 1) to study the problem status and the needs for research management of Sisaket Rajabhat university, 2) to study the factors supporting to the research management of Sisaket Rajabhat University and 3) to study the guidelines for improving the efficiency of research management of Sisaket Rajabhat university. The sample groups used in this research are divided into 2 groups; namely 1) target groups in studying the problem status and the needs for research management of Sisaket Rajabhat university that is 44 researchers who have received the research fund of education maintenance budget from university in 2019, studying from answering the questionnaire and 2) target groups in studying the factors supporting to the research management of Sisaket Rajabhat university and guidelines in research management efficiency enhancement of Sisaket Rajabhat university; namely 6 representatives of the university administrators, faculties, college, offices and 5 officers on the research stationed in the faculties / college totaling 11 persons, analyzing the qualitative data and studying from in-depth interview. The research findings are as follows: The problem status and the needs for research management of Sisaket Rajabhat university have the need in development at high level (= 4.13, = 0.46), the issue of research problem development system need ( = 4.19, = 0.48), the second is research following and supporting system ( = 4.14, = 0.55) and research proposal development system ( = 4.14, = 0.46) having the same average and research publicizing systemtoward utilization ( = 4.04, = 0.59) respectively. Factors supporting to the research administration of Sisaket Rajabhat university have 4 aspects that is 1) factor on the personnel, 2) factor on the money, 3) factor on the tools and 4) factor on the management. 3. Guidelines for increasing the efficiency of research management of Sisaket Rajabhat university consisted of 4 aspects that is 1) on the personnel, development of researchers’ potentials in beginning level, middle level and high level, 2) on the budget, supporting the research budget, developing the body of knowledge and new innovations, 3) on the structure, building cooperation, the tool readiness for supporting the research and 4) on the research management, management having the guidelines since upstream, midstream and downstream of the process to improve the research quality of university to be known and accepted in international level.